2022
DOI: 10.3390/ijms23084340
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Link between Insulin Resistance and Adrenal Incidentalomas

Abstract: Adrenal incidentalomas are incidentally discovered adrenal masses greater than one centimeter in diameter. An association between insulin resistance and adrenal incidentalomas has been established. However, the pathophysiological link between these two conditions remains incompletely characterized. This review examines the literature on the interrelationship between insulin resistance and adrenal masses, their subtypes, and related pathophysiology. Some studies show that functional and non-functional adrenal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 134 publications
0
10
0
1
Order By: Relevance
“…They propose that hyperinsulinemia caused by insulin resistance, could result in the birthing of diverse masses throughout the body, including adrenal masses. 36 Patients with NFAI had higher levels of free urinary cortisol than the healthy-adrenal group. Other previous studies 17,37,38 reported that patients with NFAI had higher THF and THS than patients without adrenal tumours.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…They propose that hyperinsulinemia caused by insulin resistance, could result in the birthing of diverse masses throughout the body, including adrenal masses. 36 Patients with NFAI had higher levels of free urinary cortisol than the healthy-adrenal group. Other previous studies 17,37,38 reported that patients with NFAI had higher THF and THS than patients without adrenal tumours.…”
Section: Discussionmentioning
confidence: 85%
“…In this line, some authors have suggested that AIs may be part of the metabolic syndrome in patients with insulin resistance. They propose that hyperinsulinemia caused by insulin resistance, could result in the birthing of diverse masses throughout the body, including adrenal masses 36 …”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have reported an increased frequency of complications, including of osteoporotic fractures, in patients with AIs/ACS [ 62 , 79 , 80 ]. Additionally, the management (short- and long-term medical and surgical strategies) needs to integrate bone status into the larger panel of cardiovascular and metabolic complications due to ACS/SCS [ 108 , 109 , 110 ], as well as generally in patients with AIs/non-functioning AIs [ 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. “Non-functional” does not necessarily mean harmless, and insulin resistance, obesity, high blood pressure, diabetes, and dyslipidaemia are identified in the same patients who display a higher risk of osteoporosis and VFs [ 118 , 119 , 120 , 121 , 122 , 123 , 124 ], as is increased arterial intima-media thickness-associated endothelial dysfunction [ 125 , 126 ], elevated uric acid [ 127 ], and pro-coagulation status [ 128 , 129 ], as well as potential elevated all-cause mortality [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations in insulin sensitivity in HAAF may be influenced by changes at the level of the adrenal gland. It is known that cortisol secreted by the adrenal glands acts on the pancreas to increase glucagon release and reduce insulin release [40]. Furthermore, it is known that the adrenal cortex and the adrenal medulla regulate the release of cortisol and adrenaline, respectively, in a synchronised bidirectional manner [41,42].…”
Section: Pancreatic Responses To Hypoglycaemia and The Relevance Of T...mentioning
confidence: 99%